Prophetic Dimensions in Caregivers’ Character with Literary and Religious Reflections from Darul Ulum for Quality Education (SDG 4) - Akhmad Fatoni; Darni Darni; Anas Ahmadi; Khuaxay Sengsouk; Silva Anggi Lestari (Journal of Current Studies in SDGs, 2026)
Objektive: To explore the prophetic dimensions reflected in the character of caregivers at Al-Hambra Darul Ulum Islamic Boarding School, Jombang, East Java, Indonesia, focusing particularly on those with a literary background. The study investigates how caregivers who are also poets influence educational patterns and character formation within the pesantren (Islamic boarding school) setting. Method: Qualitative phenomenological study employs prophetic structuralism, integrating Kuntowijoyo’s prophetic literature (humanization, liberation, transcendence) and Bourdieu’s genetic structuralism (habitus, field, capital). Data were collected through in-depth interviews with Binhad Nurrohmat, a poet and caregiver, and analyzed using Creswell’s six-step interactive model. Results: The findings reveal three interconnected dimensions of prophetic structuralism in Nurrohmat’s literary practice. In the amil dimension, he exercises moral agency by rejecting shirk, slander, and harmful writing through continuous self-evalution. In the amal dimension, poetry becomes a vehicle for outward goodness (honesty, social bonding, da’wah) and inward goodness (gratitude, trust in God, remembrance of death). In the amul dimension, engagement with sufism, Qur’anic narratives, and contemplation of death builds divine awareness. Novelty: Contributing a new theoretical framework, prophetic structuralism, that integrates literary analysis, authorial reflection, and social reception, extending Kuntowijoyo's prophetic literature beyond thematic analysis. Unlike previous studies that focus solely on textual interpretation, this framework combines authorial subjectivity and reader response to offer a more comprehensive understanding of prophetic values in literature. It also demonstrates how pesantren-based education, through caregivers with literary and religious consciousness, shapes students' resilient moral character, thereby supporting SDG 4 (Quality Education), particularly target 4.7.